Rethinking the measurement of undernutrition in a broader health context: Should we look at possible causes or actual effects - Stein, Alexander J. (International Food Policy Research Institute, 2013)
Researchers and policymakers are paying increasing attention to the nexus of hunger, malnutrition, and public health, and to the related measurement of food and nutrition security. However, focusing on proxy indicators, such as food availability, and on selected head count figures, such as stunting rates, gives an incomplete picture. In contrast, global burden of disease (GBD) studies are outcome based, they follow an established methodology, and their results can be used to derive and monitor the burden of chronic and hidden hunger (undernutrition) at the global level. Judging by this measure, the international goal of halving global hunger between 1990 and 2015 has already been achieved—which is in stark contrast to the picture that emerges if the first Millennium Development Goal’s indicator for measuring hunger is used.